Corynebacterium macginleyi: a conjunctiva specific pathogen. Issue 12 (1st December 2000) - Joussen, Antonia M; Funke, Guido; Joussen, Frank; Herbertz, Georg
Abstract : BACKGROUND: Although non-diphtherial corynebacteria are ubiquitous in nature and commonly colonise the skin and mucous membranes of humans, they rarely account for clinical infection. METHODS AND RESULTS: 10 patients with unilateral conjunctivitis are described in which Corynebacterium macginleyi was isolated. This species has only recently been reported to be exclusively isolated form ocular surfaces. C macginleyi was uniformly susceptible to topical antibiotics commonly used in ophthalmology. CONCLUSION: Despite the fact that the pathogenicity of C macginleyi is not yet assured, this micro-organism should be recognised as a potential cause of bacterial superinfections. Appropriate antibiotic therapy leads to its elimination and resolution of the conjunctivitis.